DESIGN AND IMPLEMENTATION OF A SECURED PERSONAL IDENTITY BASED ECC AND ECDSA: AN INPATIENT SYSTEM - Yuliana, Mike; Awaludinsyah, Ghandra; Pratiars, Aries; Sudarsono, Amang (European Scientific Journal, ESJ, 2015)
In this research, we developed an e-health system for cases of patient’s hospitalization. This system was integrated with an e-id based RFID. E-id contains patient’s id, secret key, and personal identity that consist of strong and weak attributes. Strong attributes will be encrypted using ECC Method, while the authentication process will verify the validity of the patientâ€™s personal identity using ECDSA method. The results show that the system which was developed has been able to protect the patient’s personal identity. This is because strong attributes have been successfully encrypted. During the authentication process, the received message was authenticated. Therefore, the system that was developed is expected to increase the trust and confidence of patients.